2019
DOI: 10.1097/hjh.0000000000001948
|View full text |Cite
|
Sign up to set email alerts
|

EPHA4 regulates vascular smooth muscle cell contractility and is a sex-specific hypertension risk gene in individuals with type 2 diabetes

Abstract: This study investigated the association of genetic variants of EPHA4, a receptor tyrosine kinase, with hypertension, and the role of EPHA4 in vascular smooth muscle cell (VSMC) contractility. Methods: Data from two human genetic studies, ADVANCE and HCHS/SOL, were analysis for association of EPHA4 single nucleotide variants (SNVs) with hypertension risks. The effect of EPHA4 signalling and sex hormones on mouse vascular smooth muscle cells contractility was assessed. Results: We identified a single-nucleotide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…In all such cases, sex hormones act in concert with these EPHs/EFNs to control BP. Some of the findings from the mouse model have been corroborated by human genetic studies, in which we revealed that some variants in the EFNB2, EFNB3, and EPHA4 genes or a related signaling molecule gene are significantly associated with hypertension in a sex-specific way (19,21,22,24,25).EPHB6 is highly expressed in the medullae of adrenal glands, which are the major source of catecholamine (CAT) in the circulation. The ambient blood CAT level reflects this hormone's effect on the homeostasis of BP (26,27).…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…In all such cases, sex hormones act in concert with these EPHs/EFNs to control BP. Some of the findings from the mouse model have been corroborated by human genetic studies, in which we revealed that some variants in the EFNB2, EFNB3, and EPHA4 genes or a related signaling molecule gene are significantly associated with hypertension in a sex-specific way (19,21,22,24,25).EPHB6 is highly expressed in the medullae of adrenal glands, which are the major source of catecholamine (CAT) in the circulation. The ambient blood CAT level reflects this hormone's effect on the homeostasis of BP (26,27).…”
mentioning
confidence: 59%
“…In the past 5 years, we have demonstrated in a series of publications (16 -25) that EPHs/EFNs are involved in regulating blood pressure (BP), which was previously unknown. We reported, using gene knockout mouse models, that although EPHB6, EFNB1, EFNB3, and EPHA4 deletion results in BP elevation (16,17,20,25), EPHB4 and EFNB2 deletion lowers it (18,19). Thus, members of EPHBs/ EFNBs are a novel yin and yang system that fine-tunes BP homeostasis.…”
mentioning
confidence: 99%
“…Ostergaard et al [54], Zi et al [55], Kunej et al [56], Van der Schueren et al [57], Jin et al [58], Emdad et al [59], Liu et al [60], Scherag et al [61], Shi and Long [62], Sharma et al [63], Parente et al [64], Saint-Laurent et al [65] and Lee [66] demonstrated that over expression of COA3, PHB (prohibitin), UQCRC1, COX4I1, IFI27, MTDH (metadherin), S100A16, SDCCAG8, GLI2, NTN1, NLGN2, FGFR3 and PTPRN2 could cause obesity, but these genes might be involved in progression of PCOS. Alsters et al [67], Lee et al [68], Shiffman et al [69], Yaghootkar et al [70], Rotroff et al [71], Cheng et al [72], Baig et al [73], Zhang et al [74], Lebailly et al [75], Ferris et al [76], Lempainen et al [77] and McCallum et al [78] presented that high expression of CPE (carboxypeptidase E), RPL13A, CERS2, CCND2, PRPF31, SARM1, PLD1, EPHA4, ARNTL2, BATF3, IKZF4 and MEN1 were associated with diabetes, but these genes might be linked with advancement of PCOS. Wang et al [79], Tian et al [80], Zhang et al [81] and Carr et al [82] demonstrated that over expression of ATP6AP2, FIS1, GRK4 and KCNQ4 were found to be substantially related to hypertension, but these genes might be essential for PCOS progression.…”
Section: Discussionmentioning
confidence: 99%
“…Several ADVANCE analyses have addressed genotypic associations with raised blood pressure [67][68][69][70] or kidney disease. 71,72 We have also identified the PROX1 gene CC genotype to be related to early-onset of diabetes.…”
Section: Genomicsmentioning
confidence: 99%